2011
DOI: 10.1128/jvi.00060-11
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Golgi Complex-Targeting Signal in the Cytoplasmic Tail of the Severe Acute Respiratory Syndrome Coronavirus Envelope Protein

Abstract: The 2003 global outbreak of progressive respiratory failure was caused by a newly emerged virus, severe acute respiratory syndrome coronavirus (SARS-CoV). In contrast to many well-studied enveloped viruses that assemble and bud at the plasma membrane, coronaviruses assemble by budding into the lumen of the endoplasmic reticulum-Golgi intermediate compartment and are released from the cell by exocytosis. For this to occur, the viral envelope proteins must be efficiently targeted to the Golgi region of the secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
125
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(133 citation statements)
references
References 53 publications
8
125
0
Order By: Relevance
“…Some of the differences in the results obtained in different studies on the same E protein may be attributable to the use of N-or C-terminal tags that have the potential for interfering with proper targeting of the E protein when overexpressed from plasmids. A Golgi-targeting sequence in the C-terminal cytoplasmic tail has also been identified for the SARS-E protein (Cohen et al, 2011) and a dilysine-like ER retention signal was identified in the C-terminal 6 amino acids of IBV E . The dilysine-like motif is not conserved in other coronaviruses, whereas the Golgi-targeting signal is conserved in beta and gammacoronaviruses.…”
Section: B Small Membrane (E) Proteinmentioning
confidence: 98%
See 2 more Smart Citations
“…Some of the differences in the results obtained in different studies on the same E protein may be attributable to the use of N-or C-terminal tags that have the potential for interfering with proper targeting of the E protein when overexpressed from plasmids. A Golgi-targeting sequence in the C-terminal cytoplasmic tail has also been identified for the SARS-E protein (Cohen et al, 2011) and a dilysine-like ER retention signal was identified in the C-terminal 6 amino acids of IBV E . The dilysine-like motif is not conserved in other coronaviruses, whereas the Golgi-targeting signal is conserved in beta and gammacoronaviruses.…”
Section: B Small Membrane (E) Proteinmentioning
confidence: 98%
“…Immunofluorescence studies in MHV Yu et al, 1994), SARS-CoV (Liao et al, 2006;Nieto-Torres et al, 2011), IBV (Corse and Machamer, 2000), and TGEV (Godet et al, 1992) infected cells demonstrate that the majority of the E protein localizes to juxtanuclear membranes. The precise origin of these juxtanuclear membranes containing E appears to vary somewhat from virus to virus and from study to study, with E being reported to colocalize with Golgi markers (Corse and Machamer, 2000) and with ER markers for IBV ; SARS-CoV E protein has been reported to colocalize with Golgi (Cohen et al, 2011;Liao et al, 2006), ER (Nal et al, 2005), or ERGIC markers (Nieto- Torres et al, 2011); MHV E protein colocalizes with ER and ERGIC markers ; TGEV E protein colocalizes with the ERGIC markers (Ortego et al, 2007). Although most studies examining E protein localization did not report E as being present on plasma membranes but rather in an intracellular membranous compartment (see above), several studies reported that a small fraction of E protein could also be detected on plasma membranes (Godet et al, 1992;Pervushin et al, 2009;Yuan et al, 2006a).…”
Section: B Small Membrane (E) Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the presence of the E protein in the viral envelope is emphasized by the fact that there are only about twenty E molecules incorporated within the virion structure (Godet et al, 1992;Liu and Inglis, 1991;Yu et al, 1994) and deletion of the protein can either completely prevent the production of detectable infectious virions (Almazán et al, 2013;Curtis et al, 2002;Ortego et al, 2007Ortego et al, , 2002 or significantly reduce infectious virus titers (DeDiego et al, 2008(DeDiego et al, , 2007Kuo et al, 2007;Kuo and Masters, 2003). The majority of the coronavirus E protein in the infected cell is localized within the secretory pathway between the membranes of the endoplasmic reticulum (ER), Golgi and intermediate compartment between them (ERGIC) (Cohen et al, 2011;Nieto-Torres et al, 2011;Venkatagopalan et al, 2015). It is in this intracellular region that additional functions mediated by various domains of the coronavirus E proteins are proposed to occur.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, a Golgi complex-targeting signal was discovered in a coronavirus responsible for severe acute respiratory syndrome. It was shown that, in the cytoplasmic tail, there is a beta-hairpin structural motif that controls Golgi complex localization [172]. Exploiting this motif could be a way of improving the targeting of the Golgi complex.…”
Section: Golgi Complexmentioning
confidence: 99%